General Collective Intelligence as Biomimicry of Nature’s Design and Manufacturing Processes - Williams, Andy (My University, 2020)
This paper explores the current limits to the complexity of design and manufacturing processes that can be reliably created or executed by humans, as well as exploring the general categories of products that can’t currently can’t reliably be manufactured as a consequence. This paper also explores how nature removes those barriers to complexity in its design and manufacturing, as well as how nature removes the barriers to the complex cooperation through which this complex design and manufacturing become sustainably viable, and how General Collective Intelligence replicates the adaptive problem solving processes by which nature does so. Finally, this paper explores why the type of products that can’t currently be manufactured, and why the patterns of complex cooperation that can’t currently be reliably executed, are both critically important, and therefore why General Collective Intelligence is critically important to the future of manufacturing.
Keywords: complex manufacturing cooperation; General Collective Intelligence; manufacturing complexity